2021
DOI: 10.3390/ijerph182010707
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Caregiver Burden of Patients with Alzheimer Disease Attending Day-Care Centres

Abstract: Nowadays, there are plenty of programs and resources to prevent caregiver burden of patients with Alzheimer’s disease. In spite of that, many caregivers suffer high levels of burden and stress, which leads to an earlier institutionalization of patients. This study aimed to explore the predictors of burden in relative caregivers of patients attending day-care centers and the moderating role of caregiver kinship in these associations. A sample of a hundred and two patient–caregiver dyads was recruited. Burden wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
1
4
0
2
Order By: Relevance
“…In one study included in this scoping review, younger caregivers with high levels of education were likely to feel more stressed when caring for PWD [10]. Another study of adult caregivers with high levels of education showed different findings, in that the caregivers reported more stress from family responsibilities than their caring role [31]. This finding may be due to limited studies involving adults, or the inherent nature of responsibilities, which often increase as people age.…”
Section: Discussionmentioning
confidence: 96%
“…In one study included in this scoping review, younger caregivers with high levels of education were likely to feel more stressed when caring for PWD [10]. Another study of adult caregivers with high levels of education showed different findings, in that the caregivers reported more stress from family responsibilities than their caring role [31]. This finding may be due to limited studies involving adults, or the inherent nature of responsibilities, which often increase as people age.…”
Section: Discussionmentioning
confidence: 96%
“…Considering that cases of dementia have been increasing worldwide, a high prevalence of caregiver burden becomes a significant and concerning issue that deserves attention for this population, as they are at risk of developing health issues. Prolonged stress caused by the continuous provision of care leads caregivers to devalue their own needs and neglect selfcare, resulting in illnesses and ultimately in neglect in providing care 4,12,13 and early institutionalization of the care recipient 14 .…”
Section: Discussionmentioning
confidence: 99%
“…This can be justified by the accumulation of roles. Caregiver burden was higher among younger family caregivers, especially those who lived with the elderly person with dementia and had other family obligations 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Considerando que os casos de demência têm aumentado em todo o mundo, uma elevada prevalência de sobrecarga entre cuidadores torna-se uma questão expressiva e preocupante, que merece um olhar voltado a esse grupo populacional, sob risco de adoecimento. O estresse prolongado, ocasionado pela prestação contínua dos cuidados leva o cuidador a desvalorizar suas próprias necessidades e a negligenciar o autocuidado, resultando em doenças e, em última instância, na negligência na prestação dos cuidados 4,12,13 e na institucionalização precoce do receptor de cuidados 14 .…”
Section: Discussionunclassified
“…Isso pode ser justificado pelo acúmulo de funções. Sobrecarga foi maior entre os cuidadores familiares mais jovens, sobretudo naqueles que residiam com a pessoa idosa com demência e que tinham outras obrigações familiares 14 .…”
Section: Discussionunclassified